Cinder Edna - Jackson, Ellen, 1943- (Lothrop, Lee & Shepard, 1994)
Cinderella and Cinder Edna, who live with cruel stepmothers and stepsisters, have different approaches to life; and, although each ends up with the prince of her dreams, one is a great deal happier than the other.